2019
DOI: 10.1523/jneurosci.2700-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Categorical Biases in Human Occipitoparietal Cortex

Abstract: Categorization allows organisms to generalize existing knowledge to novel stimuli and to discriminate between physically similar yet conceptually different stimuli. Humans, nonhuman primates, and rodents can readily learn arbitrary categories defined by low-level visual features, and learning distorts perceptual sensitivity for category-defining features such that differences between physically similar yet categorically distinct exemplars are enhanced, whereas differences between equally similar but categorica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 54 publications
6
41
0
Order By: Relevance
“…In comparison to the IPS and PFC, although the effects were generally weaker, delay-period activity in the LO showed an opposite trend, in that it was more sensitive to load-related changes in drift to particular stimulus values (i.e., to attractor strength) than it was to loadrelated changes in diffusion. This result is consistent with other demonstrations of bias in visual cognition, such as the influence of prior expectation on the representation of motion [22] and the influence of learning on representations of category boundaries in visual cortex [23]. Because our current study did not involve a learning intervention and did not focus on stimulus-specific representations, our results suggest that what we already know about the neural bases of the biasing effects of recent experience on visual cognition may extend to more trait-like "preexisting" attractor landscapes that have been sculpted through a life-time of experience with the visual world.…”
Section: Plos Biologysupporting
confidence: 92%
“…In comparison to the IPS and PFC, although the effects were generally weaker, delay-period activity in the LO showed an opposite trend, in that it was more sensitive to load-related changes in drift to particular stimulus values (i.e., to attractor strength) than it was to loadrelated changes in diffusion. This result is consistent with other demonstrations of bias in visual cognition, such as the influence of prior expectation on the representation of motion [22] and the influence of learning on representations of category boundaries in visual cortex [23]. Because our current study did not involve a learning intervention and did not focus on stimulus-specific representations, our results suggest that what we already know about the neural bases of the biasing effects of recent experience on visual cognition may extend to more trait-like "preexisting" attractor landscapes that have been sculpted through a life-time of experience with the visual world.…”
Section: Plos Biologysupporting
confidence: 92%
“…Candidate areas involved in perceptual uncertainty computations from the perceptual decision-making literature are sensory, parietal, and frontal cortex (Kiani and Shadlen, 2009;Mulder et al, 2012;Summerfield and Koechlin, 2010;Van Bergen and Jehee, 2017;Van Bergen et al, 2015). There is some evidence to suggest that categorical biases emerging from the choice history are already reflected in early visual areas (Ester et al, 2020;Nienborg and Cumming, 2009). Moreover, Peters et al (2017) showed that meta-cognitive confidence representations of choice-congruent evidence, which, as argued above, could be related to the categorical-choice bias, are distributed across multiple brain areas.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have found strong stimulus coding and category-related modulation stimulus representations during concept or perceptual learning (Ester, Sprague, & Serences, 2020;Braunlich & Love, 2019;Kuai, Levi, & Kourtzi, 2013;Mack et al, 2013;Zhang & Kourtzi, 2010;Freedman & Assad, 2006;Kourtzi, Betts, Sarkheil, & Welchman, 2005). For example, concept learning studies that used object stimuli have shown strong modulation of sensory signals in the lateral occipital cortex after learning (Braunlich & Love, 2019;Kuai et al, 2013;Mack et al, 2013).…”
Section: Discussionmentioning
confidence: 99%